COVID-19 Exposure, Stress, and Mental Health Outcomes: Results From a Needs Assessment Among Low Income Adults in Central North Carolina - Kaniuka, Andréa R.; Cramer, Robert J.; Wilsey, Corrine N.; Langhinrichsen-Rohling, Jennifer; Mennicke, Annelise; Patton, Alexandra; Zarwell, Meagan; McLean, Carmen P.; Harris, Yu-Jay; Sullivan, Sharon; Gray, Glori (Frontiers in Psychiatry, 2022)
This study focuses on identifying COVID-19 related exposure, stress, and mental health concerns in the larger Charlotte, North Carolina region, an area with many low-income and under resourced communities. A community-academic partnership conducted a regional COVID-19 needs assessment. Low-income adults (N=156) completed an online-administered survey of demographic information, COVID-19 exposure, stress, coping-related factors, and mental health. Common COVID-19 related stressors included job exposure, lost job/income, and increased home responsibilities. Elevated screening risk rates for mental health concerns were observed for post-traumatic stress (83.3%), depression (52.2%), problematic drinking (50.0%), generalized anxiety (43.0%), and suicide (40.4%). Robust mental health risk factors included COVID-19 related stress affecting close persons, fear/worry reaction to the pandemic, and use of venting as a coping strategy; protective factors included active coping and problem-focused coping beliefs. Findings are discussed with respect to informing regional public health efforts during the pandemic.